2021
DOI: 10.1002/anie.202016234
|View full text |Cite
|
Sign up to set email alerts
|

Interweaving Visible‐Light and Iron Catalysis for Nitrene Formation and Transformation with Dioxazolones

Abstract: Herein, visible-light-driven iron-catalyzed nitrene transfer reactions with dioxazolones for intermolecular C(sp 3 )-N, N = S, and N = Pb ond formation are described. These reactions occur with exogenous-ligand-free process and feature satisfactory to excellent yields (up to 99 %), an ample substrate scope (109 examples) under mild reaction conditions.I n contrast to intramolecular CÀHa midations strategies,a n intermolecular regioselective CÀHa midation via visiblelight-induced nitrene transfer reactions is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 131 publications
6
43
0
1
Order By: Relevance
“…Due to experimental challenges of analyzing the reaction progress under mechanochemical conditions, several steps have to remain descriptive at this stage. In analogy to the discussion by Bao, Yu, and co‐workers for reactions (in solution) with a 3‐phenyl substituted dioxazolone and FeCl 3 , [20b] we propose an activation of substrate 1 by coordination of FeBr 3 . Loss of CO 2 leads to a new species A , formally corresponding to an acylnitrene iron intermediate [21] .…”
Section: Methodssupporting
confidence: 67%
“…Due to experimental challenges of analyzing the reaction progress under mechanochemical conditions, several steps have to remain descriptive at this stage. In analogy to the discussion by Bao, Yu, and co‐workers for reactions (in solution) with a 3‐phenyl substituted dioxazolone and FeCl 3 , [20b] we propose an activation of substrate 1 by coordination of FeBr 3 . Loss of CO 2 leads to a new species A , formally corresponding to an acylnitrene iron intermediate [21] .…”
Section: Methodssupporting
confidence: 67%
“…In 2021, Bao and co-workers reported a protocol of ironcatalyzed nitrene transfer reaction with dioxazolones for the intermolecular C-N, N=S, and N=P bond formation under visible-light irradiation (Scheme 9). 16 The optical absorption studies revealed that the initial formation of a photoactive iron species coordinated with dioxazolone. Through a computational study, the reaction was proved to be exothermic and the spin state of the Fe/N species was found to keep in the sextet state.…”
Section: Scheme 8 Iron-catalyzed Intramolecular Aromatic C-h Oxygenationmentioning
confidence: 99%
“…Bao and co-workers disclosed an efficient and practical protocol for the intermolecular construction of C-N, N=S and N=P bonds via a Fe-catalyzed nitrene-transfer strategy from dioxazolones, which was driven by visible-light irradi-ation without the addition of an extra photosensitizer (Scheme 27). 45 A wide range of functional groups was tolerated under mild conditions. Control experiments support the fact that the reactions proceed through a radical pathway.…”
Section: Short Review Synthesismentioning
confidence: 99%